FAT CONTENT IN YOGHURTS VERSUS NON-FAT FORTIFYING–A RHEOLOGICAL AND SENSORIAL APPROACH - VASILEAN, Ina; APRODU, Iuliana; PĂTRAȘCU, Livia (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This study investigated the effect of fat content (3.5; 1.5 and 0.1 % w/w), together with total solids content on selected rheological and sensorial characteristics of yoghurt samples fermented with exopolysaccharides producing lactic acid bacteria (Streptococcus termophilus and Lactobacillus delbrueckii ssp. Bulgaricus). Rheological flow and oscillatory tests showed that all tested yoghurt samples behave like thixotropic fluids. Pronounced hysteresis areas were obtained for skimmed yoghurts with added solids (skim milk powder and lactose, 2 and 3% w/v). Higher levels of fat favoured the flow properties of the yogurt samples, enabling the formation of more stable viscoelastic gel networks. Sensorial characteristics were highly appreciated for samples with higher fat content.